Audit report and systematic review of orolingual angioedema in post-acute stroke thrombolysis. (July 2014) - Lekoubou, Alain; Philippeau, Frédéric; Derex, Laurent; Olaru, Angel; Gouttard, Michel; Vieillart, Anne; Kengne, Andre Pascal
<x content-type="archive" xml:space="preserve">Abstract</x> Rationale: Post-intravenous recombinant tissue plasminogen activator (r-tPA) orolingual angioedema (PIROLA), including the life-threatening form, is an underappreciated complication of ischaemic stroke treatment. Aims: We present an audit report and a systematic review of published observational studies on PIROLA occurrence in acute ischaemic stroke patients. Methods: Clinical files of patients treated in the stroke unit of Bourg-en-Bresse General Hospital (France) from January 2010 to December 2012 were reviewed, and MEDLINE (inception to May 2013) were searched and bibliographies/citations of retrieved articles examined for evidence of PIROLA. Results: Of the 129 acute ischaemic stroke patients treated at Bourg-en-Bresse between 2010 and 2012, four patients, all receiving angiotensin converting enzyme inhibitor (ACEI), developed a PIROLA (cumulative incidence rate: 32‰). The complication started within an hour of receiving r-tPA and integrally resolved within 3–24 hours, with antihistamines/steroid treatment in two patients. The systematic review identified 27 studies, totalising with ours, over 9050 acute ischaemic stroke patients from 12 countries, among whom 100 (cumulative incidence rate: 17‰; 95% confidence intervals: 8–26), developed a PIROLA within 6–240 minutes of receiving r-tPA, 0–100% of them occurring among patients on ACEI. The complication was contralateral to the stroke location in 47% cases, ipsilateral in 14%, and bilateral in 39%; and resolved within 24 hours with treatment in 90%. No related death was recorded. Conclusions: About 17‰ acute ischaemic stroke patients receiving r-tPA develop PIROLA, occurring essentially among those on concomitant ACEI. PIROLA occurrence should be actively monitored, particularly within the first few hours as some may require urgent lifesaving procedures.